Additional evidence from a case report supports a novel hypothesis on the association between complex regional pain syndrome and lymphedema - Melin, M. Mark; Rasmussen, John C.; Aldrich, Melissa B.; Karni, Ron J.; Fife, Caroline E.; Eckert, Kristen A. (Frontiers in Pain Research, 2025)
A previous report of 4 heterogeneous cases demonstrated that automated manual lymphatic drainage therapy (AMLDT), administered by a novel, pneumatic mat of 16 pressurized air channels that inflate and deflate sequentially to mimic the stretch and release action of manual lymphatic drainage therapy (MLD), altered lymphatic contractility and relieved pain. Near-infrared fluorescence imaging (NIRF-LI) was used 1 h before AMLDT, during 1 h of AMDLT, and 30–60 min after treatment to obtain images that could be used to determine lymphatic contractility, as measured by pulsing frequency over a given timeframe. Herein, a case of type 2 complex regional pain syndrome (CRPS, with nerve dysfunction confirmed) and lymphedema following a complex fracture on the lower leg is reported in further detail, with a discussion explaining the association between autonomic and lymphatic dysfunction and their combined contribution to the development of chronic pain. More specifically, this case provides clinical evidence of the association between autonomic nervous system dysfunction, lymphatic dysfunction, and CRPS. We believe that the regulation of lymphatic flow is a potential therapeutic pathway to alleviate the symptoms of CRPS. Further research on the association between autonomic and lymphatic dysfunction and pain is warranted, particularly in patients with CRPS and symptoms of edema following leg fractures.